Сьӧлыктэм сьӧлык: кузьмадёсъёс, веросъёс / Анатолий Перевозчиков - Перевозчиков Анатолий Аркадьевич (Удмуртия, 2017)
Экземпляры: (20200122) / Инвентарный номер: 50485 / Цена: 100.00 / Сис.шифр: С(Удм) / Авт.знак: П 27 / ГРНТИ: 17 / ББК: 84(2)